Impact of a NDUFC2 Variant on the Occurrence of Acute Coronary Syndromes - Gallo, Giovanna; Migliarino, Serena; Cotugno, Maria; Stanzione, Rosita; Burocchi, Simone; Bianchi, Franca; Marchitti, Simona; Autore, Camillo; Volpe, Massimo; Rubattu, Speranza (Frontiers in Cardiovascular Medicine, 2022)
Background. Among several potential mechanisms, mitochondrial dysfunction has been proposed to be involved in the pathogenesis of coronary artery disease (CAD).A mitochondrial complex I deficiency severely impairs cardiovascular health and contributes to CAD development.Previous evidence highlighted a key role of NDUFC2, a subunit of complex I,deficiency in the increased occurrence of renal and cerebrovascular damage in an animal model of hypertension, and of juvenile ischemic stroke occurrence in humans. Furthermore, a significant decrease of NDUFC2 mRNA was detected in peripheral blood mononuclear cells from patients experiencing acute coronary syndrome (ACS).The T allele at NDUFC2/rs23117379 variant is known to associate with reduced gene expression and mitochondrial dysfunction. Objective.In the present study we tested the impact of the T/C NDUFC2/rs23117379 variant on occurrence of ACS in a prospective cohort of CAD patients (n=260). Results. Hypertension, smoking habit, diabetes and hypercholesterolemia were present in a large proportion of patients. NSTEMI represented the most frequent type of ACS (44%, n=115), followed by STEMI (34%,n=88) and unstable angina (22%,n=57). The alleles/genotypes distribution for T/C at NDUFC2/rs23117379 revealed that the TT genotype was associated with a trend toward the development of ACS at an earlier age (TT 61±12,CT 65±12 and CC 66±11 years;p=0.051 after adjustment for gender,hypertension,smoking habit,diabetes and hypercholesterolemia) and with a significant predictive role for ACS recurrence (HR 1.671; 95% CI, 1.138-2.472; p=0.009). Conclusions.Our findings are consistent with a deleterious effect of NDUFC2 deficiency on acute coronary events predisposition and further support a role of the NDUFC2/rs23117379 variant as a genetic cardiovascular risk factor.